A rare case of retropharyngeal fibromatosis presenting with stridor - Srinivasan, Dharanya; P. Ravichandran, Subhashini; Ramasamy, Karthikeyan; Ganesan, Sivaraman; Alexander, Arun (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Stridor is one of the common emergencies in otolaryngology clinics, the usual causes being malignancies of glottis and hypopharynx. We present a rare case of stridor caused by retropharyngeal fibromatosis in an elderly patient. A 62-year-old male patient presented with complaints of breathing difficulty associated with dysphagia for one-month duration. On evaluation, he was found to have moderate stridor and a smooth mucosa-covered bulge in the posterior pharyngeal wall obscuring the endolarynx. With a working diagnosis of retropharyngeal mass causing stridor, the patient underwent an emergency tracheostomy. Initial punch biopsies from the lesion were non-diagnostic. On further evaluation by imaging and histopathological examination of incisional biopsy, we arrived at a diagnosis of giant retropharyngeal fibromatosis extending from skull base to C6. The patient underwent en-bloc trans-cervical excision of the tumor. Fibromatoses of the retropharynx is a group of rare tumor entity, which is benign, locally aggressive and recurrent. Dysphagia is the usual presentation though large tumors can present with stridor due to upper airway obstruction. Imaging and preoperative surgical planning play a crucial role in individualizing the management of these tumors due to their inaccessible location and proximity to major vasculature and nerves in the head and neck. Complete, meticulous pre-operative evaluation with imaging followed by surgical management is of paramount importance in the treatment of retropharyngeal tumors and thereby prevent its recurrence.